Intraoperative increase of portal venous pressure is an immediate predictor of posthepatectomy liver failure after major hepatectomy: a prospective study - Bogner, Andreas Georg; Reißfelder, Christoph; Striebel, Fabian; Mehrabi, Arianeb; Ghamarnejad, Omid; Rahbari, Mohammad; Weitz, Jürgen; Rahbari, Nuh Nabi (Annals of surgery, 2021)
Objectives: The aim of this study was to assess intraoperative changes of hepatic macrohemodynamics and their association with ascites and posthepatectomy liver failure (PHLF) after major hepatectomy. - Summary of Background Data: Large-scale ascites and PHLF remain clinical challenges after major hepatectomy. No study has concomitantly evaluated arterial and venous liver macrohemodynamics in patients undergoing liver resection. - Methods: Portal venous pressure (PVP), portal venous flow (PVF), and hepatic arterial flow (HAF) were measured intraoperatively pre- and postresection in 67 consecutive patients with major hepatectomy (ie, resection of ≥3 liver segments). A group of 30 patients with minor hepatectomy served as controls. Liver macrohemodynamics and their intraoperative changes (ie, Δ) were analyzed as predictive biomarkers of ascites and PHLF using Fisher exact, t test, or Wilcoxon rank sum test for univariate and logistic regression for multivariate analyses. - Results: Major hepatectomy increased PVP by 26.9% (P = 0.001), markedly decreased HAF by 40.7% (P < 0.001), and slightly decreased PVF by 13.4% (P = 0.011). Minor resections had little effects on hepatic macrohemodynamics. There was no significant association of liver macrohemodynamics with ascites. While middle hepatic vein resection caused higher postresection PVP after right hepatectomy (P = 0.04), the Pringle maneuver was associated with a significant PVF (P = 0.03) and HAF reduction (P = 0.03). Uni- and multivariate analysis revealed an intraoperative PVP increase as an independent predictor of PHLF (P = 0.025). - Conclusion: Intraoperative PVP kinetics serve as independent predictive biomarker of PHLF after major hepatectomy. These data highlight the importance to assess intraoperative dynamics rather than the pre- and postresection PVP values.